2020
DOI: 10.3390/biology9030058
|View full text |Cite
|
Sign up to set email alerts
|

Silicates of Potassium and Aluminium (Kaolin); Comparative Foliar Mitigation Treatments and Biochemical Insight on Grape Berry Quality in Vitis vinifera L. (cv. Touriga National and Touriga Franca)

Abstract: Grapevine physiology is influenced by several environmental factors, such as temperature, precipitation, potential evapotranspiration, and sunshine hours. Due to climatic changes, effects in grapevine physiology and consequently on the grape berry composition and quality have been observed. This work aims to make a comparative study of the effect of foliar mitigation treatment with kaolin (5%) and potassium silicates (0.1% and 0.05%) on the grape berry quality; namely on berry weight, pH, probable alcohol, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…However, particle film technology has shown beneficial effects on several fruit quality traits, preserving berry acidity, promoting a balanced synthesis of secondary metabolites and sugar transport throughout ripening. 21,28 In agreement, the results revealed that kaolin application decreased fruit SS content under summer stress conditions (Table 2) and slightly preserved berry acidity, mainly tartaric acid, with no effects on pH at the last stage of maturation, as recently described by Singh et al 52 These attributes are highly appreciated by the wine industry owing to their potential to sustain wine balancing and quality. 57 Moreover, several studies have shown a yield increase in several crops after kaolin application, which was correlated to increasing growing-season temperatures, highlighting the efficiency of kaolin in mitigating environmental stresses.…”
Section: Season Stagesupporting
confidence: 89%
See 1 more Smart Citation
“…However, particle film technology has shown beneficial effects on several fruit quality traits, preserving berry acidity, promoting a balanced synthesis of secondary metabolites and sugar transport throughout ripening. 21,28 In agreement, the results revealed that kaolin application decreased fruit SS content under summer stress conditions (Table 2) and slightly preserved berry acidity, mainly tartaric acid, with no effects on pH at the last stage of maturation, as recently described by Singh et al 52 These attributes are highly appreciated by the wine industry owing to their potential to sustain wine balancing and quality. 57 Moreover, several studies have shown a yield increase in several crops after kaolin application, which was correlated to increasing growing-season temperatures, highlighting the efficiency of kaolin in mitigating environmental stresses.…”
Section: Season Stagesupporting
confidence: 89%
“…Therefore, the differences regarding stress severity found between growing seasons might influence the effectiveness of kaolin in balancing berry ripening and quality potential in red grapevine varieties grown in Mediterranean-like climate regions. Nonetheless, kaolin application effects in grapevines can also vary according to the variety under study, 32,52 because the accumulation of several stress-related metabolites and the hormonal content differed among varieties. One of the expected impacts of climate variability in temperate climate regions is the earlier onset of several phenological stages.…”
Section: Discussionmentioning
confidence: 99%
“…Control group was sprayed with dionized water and the treatment groups were sprayed with AlCl 3 and MgSO 4 solutions. One treatment group was sprayed using 0.2% AlCl 3 solution, and the other treatment was spraying using 2% MgSO 4 solution [ 12 , 60 , 61 ]. We collected leaves in a time-course experiment after solution exposure (0, 4, 8, 12, 24, 48, and 96 h).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, it was also observed that chitosan application not only induced the synthesis of phenolic compounds but also acted as a facilitator of phenolic transfer from leaves towards grape berries. Furthermore, the application of other foliar mitigation treatments (kaolin (5%) and potassium silicates (0.1 and 0.05%)) influenced the grape berry quality, namely the concentration of total anthocyanins and monomeric anthocyanins [ 135 ].…”
Section: Red Fruits Compositionmentioning
confidence: 99%